2015
DOI: 10.4236/ajps.2015.618285
|View full text |Cite
|
Sign up to set email alerts
|

Nursery Fertilizer Application Increases Rice Growth and Yield in Rainfed Lowlands with or without Post-Transplanting Crop Stress

Abstract: In rainfed lowlands, the beneficial effects on rice (Oryza sativa) yield from fertilizing the seedling nursery may depend on the occurrence of water and nutrient stress after transplanting into the mainfield. The aim of the study was to test the effect of seedling age and nursery fertilisation on rice yield when plants experienced nutrient and water stress regimes after transplanting. The first experiment, conducted during the wet season in a low-fertility rainfed lowland field in south-east Cambodia, examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Herein, we suggested that TUAT-1 inoculation had the higher tiller biomass production as a result of vigorous early growth and early leaf expansion at tillering stage. Similar responses to fertilizer addition at the nursery stage were reported by Ros et al [29] and Panda et al [30]. Increased tiller number and tiller biomass have been reported for rice plants treated with PGPR [31].…”
Section: Discussionsupporting
confidence: 84%
“…Herein, we suggested that TUAT-1 inoculation had the higher tiller biomass production as a result of vigorous early growth and early leaf expansion at tillering stage. Similar responses to fertilizer addition at the nursery stage were reported by Ros et al [29] and Panda et al [30]. Increased tiller number and tiller biomass have been reported for rice plants treated with PGPR [31].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies suggest that the application of small-dose nutrient resources to a nursery bed increases rice yields, especially for nutrient-deficient soils (Ros, Bell & White, 1997;Ros, White & Bell, 2015;Vandamme, Wissuwa, Rose, Ahouanton & Saito, 2016). Ros et al (2015) demonstrated that fertilizer application to nurseries increased rice yield in the low-fertility, sandy lowlands of Cambodia, reporting yield gains of 0.09-0.21 t ha -1 under well-watered conditions and 0.18-0.32 t ha -1 under water-stressed conditions.…”
Section: Improvement Of Ae N With Small-dose Fertilizer Supplementationmentioning
confidence: 99%
“…Previous studies suggest that the application of small-dose nutrient resources to a nursery bed increases rice yields, especially for nutrient-deficient soils (Ros, Bell & White, 1997;Ros, White & Bell, 2015;Vandamme, Wissuwa, Rose, Ahouanton & Saito, 2016). Ros et al (2015) demonstrated that fertilizer application to nurseries increased rice yield in the low-fertility, sandy lowlands of Cambodia, reporting yield gains of 0.09-0.21 t ha -1 under well-watered conditions and 0.18-0.32 t ha -1 under water-stressed conditions. The amount of fertilizer applied to the nursery bed was equivalent to merely 2.7 kg N per hectare in the main field, which resulted in substantially high AE N (33-78 kg kg −1 and 67-119 kg kg −1 in well-watered and waterstressed conditions, respectively), as estimated from the ratio of seeding density to the transplanted density (see Estimated AE N with microdose application technique in Table 1).…”
Section: Improvement Of Ae N With Small-dose Fertilizer Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, micro-dosed and localized P applications were examined in several crops by applying P fertilizer in root zones where P is readily accessible to the plants, instead of conventional application via broadcasting or incorporation. Studies reported that this technique increases rice yield and improves P fertilizer use efficiency, particularly in P-deficient soils in the tropics, e.g., placement of P in a planting hole for the upland rice production system [3,[6][7][8] and application to a nursery bed for the lowland rice production system [9,10].…”
Section: Introductionmentioning
confidence: 99%